2007
DOI: 10.1021/ja0760980
|View full text |Cite
|
Sign up to set email alerts
|

Rolling Circle Enzymatic Replication of a Complex Multi-Crossover DNA Nanostructure

Abstract: Nature has evolved replicable biological molecules, such as DNA, as genetic information carriers. The replication process is tightly controlled by complicated cellular machinery. It is interesting to ask if artificial DNA nano-objects with a complex secondary structure can be replicated in the same way as simple DNA double helices. Here we demonstrate that paranemic crossover DNA, a structurally complicated multi-crossover DNA molecule, can be replicated successfully using Rolling Circle Amplification (RCA). T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
70
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(73 citation statements)
references
References 20 publications
1
70
0
2
Order By: Relevance
“…This is an inspiring accomplishment, although the long strand did not form a complete nanostructure itself without the aid of the short strands. We recently reported the replication of a four-arm DNA nanojunction and a paranemic cross-over (PX) DNA molecule, using rolling-circle amplification (RCA)-based enzymatic methods (21)(22). The rolling-circle mechanism is also involved in the replication of bacteriophage genomes and bacterial plasmids in vivo, so this result suggested that it might be possible to replicate DNA nanostructures by using viruses and bacteria.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This is an inspiring accomplishment, although the long strand did not form a complete nanostructure itself without the aid of the short strands. We recently reported the replication of a four-arm DNA nanojunction and a paranemic cross-over (PX) DNA molecule, using rolling-circle amplification (RCA)-based enzymatic methods (21)(22). The rolling-circle mechanism is also involved in the replication of bacteriophage genomes and bacterial plasmids in vivo, so this result suggested that it might be possible to replicate DNA nanostructures by using viruses and bacteria.…”
mentioning
confidence: 99%
“…The rolling-circle mechanism is also involved in the replication of bacteriophage genomes and bacterial plasmids in vivo, so this result suggested that it might be possible to replicate DNA nanostructures by using viruses and bacteria. In fact, such a possibility was proposed previously (22)(23). Moreover, DNA containing a designed hairpin structure has been incorporated into a vector as the substrate for a rolling-circle transcript to produce RNA ribozymes in Escherichia coli cells (24).…”
mentioning
confidence: 99%
“…In this work, we utilized the polymerase chain reaction (PCR), a method based on biological principles, to synthesize two-dimensional DNA nanomeshes; enzymes have previously been used as post-treatments after structural formation, such as rolling circle enzymatic replication, 12,13 but not been applied for directing self-assembly of DNA building blocks. Using the PCR processes, we successfully fabricated DNA nanomeshes and controlled pore sizes of the resulting nanomeshes by varying template DNA lengths.…”
Section: Forward Primermentioning
confidence: 99%
“…[14][15][16][17][18]23,24 Their structural information has not been drawn yet in detail, but McLaughlin suggested an idealized, periodic DNA lattice with regular and defined pores. 12 We postulate that the structures were composed of many self-assembled nanomeshes with a broad range of size scales. It also should be noted that there would be a possibility of incomplete elongation of all three arms; that is, only one or two of three arms were elongated in some cases, which makes the nanomeshes disconnected.…”
Section: Forward Primermentioning
confidence: 99%
“…Two different dsDNA sequences were cloned into a phagemid vector containing a bacteriophage M13 origin of replication. In their single-stranded form, these sequences had been shown to fold via intramolecular interactions into an immobile Holliday junction or a paranemic cross-over motif, respectively (8,9). This phagemid construct was propagated in bacterial cells, and superinfection of a helper phage that expresses the replication machinery led to selective copying of 1 strand of the phagemid vector via rolling circle replication.…”
mentioning
confidence: 99%